THE INFLUENCE OF REINFORCEMENT AND MOTIVATION ON STUDENTS’ READING ABILITY - Ria Irnasari (Universitas PGRI Palembang, 2022)
The objective of this study is to determine the influence of teachers’ classroom reinforcement on the students reading ability, determine the influence of motivation on the students’ reading ability and to determine the influence of teachers’ classroom reinforcement and motivation simultaneously on the students’ reading ability. This study was conducted on SMAN 16 OKI. The sample consisted of 30 students who were divided into two classes, each classes consisted 15 students. Samples were taken by random sampling technique. The method used in this study is Expose Facto with simple regression and multiple regression. the result of the influence coefficient between teachers’ classroom reinforcement and students’ reading ability showed that level of significant was 0.041 < 0.05. Consequently,itis a significant influence of teachers’ classroom reinforcement on the elevenths grade students reading ability. The result of the influence coefficient between student’s motivation and students’ reading ability showed that level of significant was 0.036< 0.05. Consequently there is a significant influence of teachers’ classroom motivation on the elevenths grade students’ reading ability. The result of the influence coefficient between teachers’ classroom reinforcement and motivation on the students’ reading ability showed that level of significant was 0.046 < 0.05. Consequently, there are significant influences of teachers’ classroom reinforcement and motivation on the elevenths grade students reading ability.